2021
DOI: 10.1111/desc.13149
|View full text |Cite
|
Sign up to set email alerts
|

The song, not the singer: Infants prefer to listen to familiar songs, regardless of singer identity

Abstract: for their assistance transcribing mothers' song features. This research was supported by an Insight Grant (Grant # 435-2019-0202) from the Social Sciences and Humanities Research Council (SSHRC) to EKJ and LKC, Research Highlights• Familiar songs recruited more infant attention, encouraged more rhythmic movement, and resulted in less sympathetic nervous system activation than unfamiliar songs • Stranger's song renditions had comparable behavioral and electrodermal effects as mother's song renditions, even when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…Children also smiled more in response to their favorite compared to unfamiliar music, even though the favorite music was played at a different tempo from what they were used to hearing. Paralleling laboratory research with younger infants (Kragness, Johnson, & Cirelli, 2022), we also found that children smiled more frequently on trials when they danced more, highlighting the connection between musical movement and expressions of joy in early life.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Children also smiled more in response to their favorite compared to unfamiliar music, even though the favorite music was played at a different tempo from what they were used to hearing. Paralleling laboratory research with younger infants (Kragness, Johnson, & Cirelli, 2022), we also found that children smiled more frequently on trials when they danced more, highlighting the connection between musical movement and expressions of joy in early life.…”
Section: Discussionsupporting
confidence: 72%
“…These findings contribute to a growing body of work documenting the social-emotional importance of familiar music in early childhood, and the flexibility with which young children can identify familiar music. For example, 9- to 12-month-old infants listen longer and move rhythmically more when listening to familiar songs, whether they are sung by their own caregiver or by a stranger (Kragness, Johnson, & Cirelli, 2022), and toddlers help a stranger more if they are familiar with a song she is singing (Cirelli & Trehub, 2018). Songs are proposed to be strong signals for shared culture and group belonging, and this early responsiveness to favorite songs suggests that young children already integrate these songs into their musical identities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children also smiled more frequently in response to their favorite compared to unfamiliar music, even though the favorite music was played at a different tempo from what they were used to hearing. Paralleling laboratory research with younger infants (Kragness, Johnson, & Cirelli, 2022), we also found that children smiled more frequently on trials when they danced more, highlighting the connection between musical movement and expressions of joy in early life.…”
Section: Discussionsupporting
confidence: 72%
“…According to caregiver report, half of infants "dance" to music by 6 months, and 90% by their first birthday (Kim & Schachner, 2019). In experimental contexts, infants move more to music or rhythms than speech and more to familiar than unfamiliar songs (Fujii et al, 2014;Kragness et al, 2022;Zentner & Eerola, 2010). These musical movements are frequently accompanied by smiling and laughter (Kragness et al, 2021).…”
Section: Musical Groove Shapes Children's Free Dancingmentioning
confidence: 99%